This is a linear equation. The value x = -1 is the solution to this equation.
Chat with our AI personalities
6-4x = 7x-9x-2 6-4x = -2x-2 Add 4x to both sides: 6 = 2x-2 Add 2 to both sides: 8 = 2x Divide both sides by 2: 4 = x
7x-4=x+2 7x=x+2+4 7x=x+6 7x-x=6 6x=6 X=1
7x + 6
Given these two equations: 7x - 2y = 6 9x - 3y = 6 you start my taking either one of them, and solving it for either x or y. Let's start with the first one, and solve for y: 7x - 2y = 6 ∴ -2y = 6 - 7x ∴ y = -3 + 7x / 2 Now you can take that definition of y, and substitute it into the other equation: 9x - 3y = 6 ∴ 9x - 3(-3 + 7x / 2) = 6 We now have an equation with only one variable, x, and can solve it as follows: 9x - 3(-3 + 7x / 2) = 6 ∴3x + 3 - 7x/2 = 2 ∴3x - 7x/2 = -1 ∴6x/2 - 7x/2 = -1 ∴-x/2 = -1 ∴x = 2 Finally, you can take that value of x, and plug it into either of the original equations in order to calculate y: 7x - 2y = 6 ∴14 - 2y = 6 ∴-2y = -8 ∴y = 4 You can then confirm that this is correct, by plugging those values into the other equation to see if they hold true: 9x - 3y = 6 ∴9(2) - 3(4) = 6 ∴18 - 12 = 6 ∴6 = 6 And since that holds true, you know your answer is correct. x is equal to 2, and y is equal to 4. Note that you can start by solving for either x or y, with either of the original equations. It doesn't matter which combination you start with. The key technique here is to solve one of the equations for either x or y, and then take that solution and plug it into the other equation.
you begin with -7x+y=-20 and 9x-3y=36 7x-7x+y=-20+7x (add 7x to both sides) y=7x-20 (simplify) 9x-9x-3y=36-9x (subtract 9x from both sides) -3y/-3=36/-3-9x/-3 (divide both sides by -3) y=3x-12 (simplify) y=y so 7x-20=3x-12 7x+20-20=3x-12+20 (add 20 to both sides) 7x=3x+8 (simplify) 7x-3x=3x-3x+8 (add 3x to both sides) 4x=8 (simplify) 4x/4=8/4 (divide by 4 on both sides) x=2 (simplify) 9(2)-3y=36 (plug in 2 for x) 18-3y=36 (simplify) 18-18-3y=36-18 (subtract 18 from both sides) -3y=18 (simplify) -3y/-3=18/-3 (divide by -3 on both sides) y=-6 (simplify) the point is 2,-6 (x,y)